Hepatitis B virus candidate subgenotype I1 varies in distribution throughout Guangxi, China and may have originated in Long An county, Guangxi1. Issue 5 (18th March 2013) - Li, Guo‐Jian; Hue, Stéphane; Harrison, Tim J.; Yang, Jin‐Ye; Chen, Qin‐Yan; Wang, Xue‐Yan; Fang, Zhong‐Liao
Abstract Sequencing of the complete hepatitis B virus (HBV) genomes from Vietnam, China and Laos led to the identification of a complex recombinant, referred to initially as an aberrant genotype and later proposed to be a new genotype, I. However, epidemiological data regarding this new genotype are lacking. A cross‐sectional study was carried out to investigate the epidemiology of HBV candidate genotype I in Guangxi, China using stratified, random cluster sampling. Four thousand five hundred thirteen subjects were recruited from five counties within Guangxi. Three genotypes, B, C, and I, were identified with a prevalence of 32.6% (114/350), 64% (224/350), and 3.4% (12/350), respectively. All the genotype I isolates belong to candidate subgenotype I1 and were found in Bing Yang (15.3%, 9/59) and Na Po (5.0%, 3/60) counties only. The prevalence of this subgenotype is significantly higher in males (5.1%, 10/195) than in females (1.3%, 2/155; X2 = 3.959, P < 0.05) but does not differ significantly with age. It was found in the Han (4.5%, 9/201) and Zhuang (3.1%, 3/97) ethnic populations only. There is no significant difference from other genotypes in the prevalence of HBV serological markers. Phylogeographic analysis revealed that genotype I1 likely arose in Long An county, then spread later to Bing Yang, Na Po counties and elsewhere in southeast Asia. In conclusion, the distribution of candidate genotype I within Guangxi is not even and it is highly endemic in some counties. Its prevalence is associated with gender and ethnicity. Subgenotype I1 likely originated in Long An county. J. Med. Virol. 85:799–807, 2013. © 2013 Wiley Periodicals, Inc.